Effect of Massage Effleurage on The Intensity of Labor Pain During Phase 1 of Active Phase - Adelia Putri Widyani; Fania Nurul Khoirunnisa; Nasriyah Nasriyah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to determine the effect of effleurage massage on the intensity of labor pain during the first active phase among mothers giving birth at Sunan Kudus Islamic Hospital. It was hypothesized that the application of effleurage massage would significantly reduce the intensity of labor pain. Research Method: This study used a pre-experimental one-group pretest-posttest design. A total of 46 mothers in the first active phase of labor were selected using purposive sampling. Pain intensity was measured before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using univariate analysis and the Wilcoxon test after the Shapiro-Wilk normality test indicated a non-normal distribution. Results and Discussion: The mean pain score decreased from 3.59 before the intervention to 2.74 after the intervention. The Wilcoxon test result showed p = 0.000 (p < 0.05), indicating a significant effect of effleurage massage on reducing labor pain intensity. These findings suggest that effleurage massage is an effective, safe, and simple non-pharmacological intervention for improving maternal comfort during labor. Implications: The findings support integrating effleurage massage into routine midwifery care. Further studies with control groups and larger sample sizes are recommended to strengthen evidence of its clinical effectiveness.